Impacts of Stress, Emotions, and Personality Traits on Psychosomatic Diseases: A Focus on Asthma and Cardiovascular Conditions - Yongmei, Hou (Current Progress in Arts and Social Studies Research Vol. 10, 2025)
Background: The incidence rates of psychosomatic diseases are increasing year by year, but the biomedical model cannot fully explain the pathogenesis, and the therapeutic effect is not ideal. Objective: Taking asthma and cardiovascular diseases as examples, the objective is to understand the progress of the impacts of three major psychological factors including stress, emotions, and personality traits on psychosomatic diseases. Methods: A literature search is used to retrieve Chinese or English survey reports and randomized controlled trial reports of the influences of stress, emotion, or traits of personality on asthma or cardiovascular illnesses from CNKI, Google Scholar, and PubMed. Results: Twenty-nine papers are included. Stress, emotions, and personality traits are important predictive variables for clinical parameters such as the onset, treatment compliance, severity, and recurrence frequency. Conclusion: Previous studies have provided useful opinions on the impacts of stress, emotions, and personality traits on psychosomatic diseases, with good theoretical and practical value. However, research methods need to be improved.